A torch against the night a novel - Tahir, Sabaa (Razorbill, 2016)
After the events of the Fourth Trial, Martial soldiers hunt the two fugitives as they flee the city of Serra and undertake a perilous journey through the heart of the Empire
Ember in the ashes
Keywords: Laia (Fictitious character) -- Fiction; Elias (Fictitious character) -- Fiction; Fugitives from justice -- Fiction; Brothers and sisters -- Fiction; Fantasy; Romance fiction; Fugitives from justice -- Juvenile fiction; Prisons -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Jugendbuch